ANALISIS BIAYA INVESTASI PERKERASAN LENTUR DAN PERKERASAN KAKU (Studi Kasus Pada Ruas Jalan Akses Rusun PPI_TPI Romokalisari Surabaya) (Jurnal Spesialis Teknik Sipil (JSpTS), 2022)
Roads are the main means of transportation to reach a destination from one place to another. The research objective is to find the project design and project costs for the rigid pavement for the flexible pavement on the access road of Rusun TPI-PPI Romokalisari Surabaya, and find a comparison of project costs. Comparison of the cost of a rigid pavement project against Flexible pavement on the access road of the Rusun TPI-PPI Romokalisari Surabaya for a period of 10 and 20 years. Data collection techniques using secondary. Data analysis in this study uses a technical analysis of the comparison of flexible pavement and rigid pavement in terms of cost. Based on the results of the technical analysis of the following flexible road pavement projects: 1) AC-WC Layer = 5 cm; 2) AC-BC layer = 5 cm; 3) 100% Class A (CBR) Subgrade Soil = 30 cm. Rigid pavement has a thickness of concrete plate K. 400 = 28 cm, Base layer Class A = 20 cm, Land Concrete K. 125 = 15 cm. Likewise, the results of Dowel and Tiebar rigid pavement test length Dowel Iron = 45 Cm, ​​Spacing Distance = 30 Cm, Ruji Diameter = 32 mm. While the Calculation Results of Tie Bar Length of Iron Tie Bar = 84 Cm, Distance Between Tier Bars = 60Cm, Diameter of Tie Bar = 20mm. Construction costs Rigid Pavement in terms of the planned age of 10 Years of the planned age of 10 and 20 years /(UR.20) which has lower costs compared to the flexible pavement of Rp. 9,924,703,104.44 or 19.88%. /(UR.10) has a lower cost compared to rigid pavement of Rp. 1,202,554,040.87 or 7.30%. Similarly, rigid Pavement is also recommended in terms